1999
DOI: 10.1080/080352599750030059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on cerebrospinal fluid levels of metabolites of biopterin and biogenic amines

Abstract: We identified an age effect on biopterin and biogenic amine metabolites in the cerebrospinal fluid from 56 neurologically normal patients, aged 1 mo to 80 y. The levels of total and reduced forms of biopterin, homovanillic acid, and 5-hydroxyindoleacetic acid were found to peak during the first year of life. The levels of these metabolites then gradually decreased, plateauing at the age of 20 y. We found significant correlations between biopterin, homovanillic acid, and 5-hydroxy-indoleacetic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
2
6
1
Order By: Relevance
“…This finding has been explained by the presence of large amounts of the key enzymes regulating both metabolic pathways during the mitosis, neurogenesis, migration and network formation of dopamine and serotonin neurons in foetus brain (Sladek et al, 1995). In agreement with previous studies (Hyland et al, 1993;Komori et al, 1999), we also observed a negative association between all BA and the age of controls. This finding led us to stratify reference values into six groups according to age.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This finding has been explained by the presence of large amounts of the key enzymes regulating both metabolic pathways during the mitosis, neurogenesis, migration and network formation of dopamine and serotonin neurons in foetus brain (Sladek et al, 1995). In agreement with previous studies (Hyland et al, 1993;Komori et al, 1999), we also observed a negative association between all BA and the age of controls. This finding led us to stratify reference values into six groups according to age.…”
Section: Discussionsupporting
confidence: 94%
“…This finding led us to stratify reference values into six groups according to age. We observed significantly higher 5-HIAA and HVA values in controls younger than 1 month compared with controls of 2-5 months (Table 2), in contrast to previously reported reference values (Hyland et al, 1993;Komori et al, 1999), which included larger ageintervals for the reference groups. It is likely that the different number of controls studied and the age-distribution of them may explain these differences.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…As oxidized pterins are fluorescent while their reduced counterparts are not, the most widely used method for pterin determination in CSF requires carrying out two HPLC (high performance liquid chromatography) runs coupled to fluorescence detection (FD) including two off-line iodine oxidation procedures for complete analysis. The first run involves oxidation under acidic conditions of both BH4 and BH2 into biopterin (B), and NH2 into neopterin (N) prior to injection into the chromatograph. The second run involves the oxidation under alkaline conditions of BH2 into B and BH4 into pterin (P).…”
mentioning
confidence: 99%